Pengaruh Persepsi Kesesakan Terhadap Psychological Well-Being Pada Penghuni Rumah Susun Di Kota Makassar - Gusmini Gusmini; Basti Tetteng (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Perception of crampedness is an individual's subjective feeling of limited space due to the density of the physical environment. This study aims to determine the effect of perceptions of overcrowding on psychological well-being in flat occupants in Makassar City. The population of this study were residents of the Mariso Flats in Makassar City. The number of research subjects was 158 people who were taken using the accidental sampling technique. The characteristics of the subjects in this study were residents of flats aged 18-40 years. The data analysis method used in this study is simple linear regression analysis. The results of the data analysis that has been carried out show that there is an influence of perceptions of overcrowding on psychological well-being of the residents of flats in Makassar City (p=0.000 R square -0.130). The effective contribution of the distress variable to the psychological well-being variable is 13.0%, which is shown from the value of R square = 0.130.